Validity of Screening for Pre-Diabetes and Type2 DM in Patients Presenting with Oral Symptoms - Dr. T MuthuVel; Dr. S. Karthikeyan (International Journal of Medical Research and Review, 2021)
Introduction: Type 2 DM is a major health problem in the present world with its high micro and macrovascular complications leading to increased mortality and morbidity. Our diagnosed T2DM represents the tip of the iceberg, where the hidden part places a vital challenge to the health care system.Objectives: Various risk factors are identified to screen the population for diabetes which is still an incomplete list hence we aimed to identify the dental illness as a potent risk factor to screen T2DM and Prediabetes.Methodology: This is an observational study in which 92 patients attending to dental clinic except for traumatic problems were screened for T2DM with random blood sugar and HbA1c.Results: In our study we observed 22.8% pre-diabetic and 8.8% with newly diagnosed T2DM among the study population. Chronic periodontitis was accounting for more than 60% of the subjects presenting dental illness.Conclusion: In our study we conclude that dental illness to be accounted as a potent risk factor for T2DM/Pre-Diabetes